GNSS e droni aerei: un connubio vincente per applicazioni di telerilevamento, sorveglianza, sicurezza e logistica - Marco Lisi (mediaGEO soc. coop., 2021)
GNSS and Unmanned Aerial Systems (UASs) are a winning synergy in many applications: remote sensing, security, mapping, surveillance, and logistics.